Clinical Characteristics and Outcome of Hospitalized COVID-19 Patients in a MERS-CoV Endemic Area - Mazin Barry; AbdulEllah AlMohaya; Ali AlHijji; Layan Akkielah; Abdulaziz AlRajhi; Fahad Almajid; Aynaa Alsharidi; Fatimah S. Al-Shahrani; Naif H. Alotaibi; Awadh Alanazi; Leen Ghonem; Abdulkarim Alhetheel; et al. (Springer, 2020)
Background: The Kingdom of Saudi Arabia (KSA) reported 170,639 cases and 1430 deaths from COVID-19 since the first case emerged in the country on March 2 through June 25, 2020. The objective of this report is to describe the characteristics and outcome observed among 99 hospitalized COVID-19 patients in the largest academic hospital in KSA, and assess co-infection with the Middle East Respiratory Syndrome Coronavirus (MERS-CoV). Methods: This single-center case series data included select epidemiological, clinical, radiological features and laboratory findings of all confirmed hospitalized cases of COVID-19 in King Saud University Medical City (KSUMC), Riyadh, KSA, from March 22 until May 31, 2020, followed through June 6, 2020. We conducted retrospective analysis of listed data from 99 hospitalized patients and present characteristics and factors associated with severity in percentages and univariate odds ratios. Cases were confirmed using nasopharyngeal or throat swab by real-time Reverse Transcriptase Polymerase Chain Reaction (RT-PCR) for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), and MERS-CoV by RT-PCR. Results: The 99 hospitalized COVID-19 patients included in this analysis constitute 16% of 632 positive SARS-CoV-2 among 6633 persons who were tested at the KSUMC (positivity rate, 9.4%). MERS-CoV PCR was negative in all 99 patients tested. The majority of these 99 hospitalized patients were males (66%), had a mean age of 44 years (range, 19-87), and a quarter (25.3%) were health care workers. Patients with comorbid conditions accounted for 52.5% of patients including the 8.1% who were asymptomatic; diabetes mellitus being the most frequent (31.3%), followed by hypertension (22.2%). The most common presenting symptoms were fever (67.7%), cough (60.6%), dyspnea (43.4%), upper respiratory symptoms (27.3%), fatigue (26.3%), diarrhea (19.2%) and loss of smell (9.1%). The clinical conditions among these 99 patients included upper respiratory tract infection (47.5%), abnormal chest X-ray, lymphopenia, high inflammatory markers a fifth (21%) of patients had moderate pneumonia, while 7% had severe pneumonia with 22.2% requiring admission to the intensive care unit and 12.1% died. Late presentation with severe disease, an abnormal chest X-ray, lymphopenia, high inflammatory markers (C-reactive protein, ferritin, and procalcitonin), and end organ damage (high creatinine or high aspartate aminotransferase) were predictors for admission to critical care unit or died. Conclusion: We observed no MERS-CoV co-infection in this early cohort of hospitalized COVID-19 patients who were relatively young, more than half had comorbid conditions, presented with fever and/or cough, an abnormal chest X-ray, lymphopenia, and high inflammatory markers. Given MERS-CoV endemicity in the country, co-monitoring of MERS-CoV and SARS-CoV-2 coinfection is critical.